Loss to follow-up tuberculosis treatment and associated factors among adults attending at public health facilities in Warder District, Somali Regional State, Eastern Ethiopia - Mohammed Birhane; Shambel Mekonnen; Tariku Dingeta; Zelalem Teklemariam (Frontiers Media S.A., 2023)
BackgroundTuberculosis is a major public health problem worldwide, particularly in resource-limited countries. Loss of follow-up during treatment is one of the major obstacles in the fight against tuberculosis, which has serious implications for patients, their families, communities, and health service providers.PurposeTo assess the magnitude of the loss to follow-up tuberculosis treatment and associated factors among adults attending public health facilities in Warder District, Somali Regional State, eastern Ethiopia from November 02-17, 2021.MethodsA 5-year (from 1 January 2016 to 31 December 2020) retrospective study was conducted on 589 adult tuberculosis treatment records. Data were collected using a structured data extraction format. Data were analyzed using STATA version 14.0 statistical package. Variables with P < 0.05 in the multivariate logistic regression analysis were considered statistically significant.ResultsA total of 98 (16.6%) TB patients failed to follow up with their treatment. Age between 55 and 64 years (AOR = 4.4, 95% CI: 1.9-9.9), being male (AOR = 1.8, 95% CI: 1.1-2.9), living more than 10 km away from a public health facility (AOR = 4.9, 95% CI:2.5-9.4), and having a history of tuberculosis treatment (AOR = 2.3, 95% CI: 1.2-4.4) were associated with a higher likelihood of not following up, while having a positive initial smear result (AOR = 0.48, 95% CI: 0.24-0.96) was associated with a lower probability of not following up.ConclusionOne out of six patients was lost to follow-up after initiating their tuberculosis treatment. Hence, improving the accessibility of public health facilities with a special focus on older adults, male patients, smear-negative patients, and retreatment cases is highly warranted among TB patients.